Pemanfaatan Simbiosis Mikroorganisme B-DECO3 dan Mikroalga Chlorella sp untuk Menurunkan Pencemaran Limbah Cair Pabrik Kelapa Sawit - Yelmira Zalfiatri; Fajar Restuhadi; Taufiq Maulana (Universitas Riau, 2017)
The purpose of this research was to get the best treatment addition of microorganisms B-DECO3 as a reducing agent contamination of waste pollution palm factory with the addition of microalgae Chlorella sp. This research used a Completely Randomized Design (CRD)with 5 treatments and 3 replications. The treatment used against waste pollution palm factory was P0 (without addition of B-DECO3 microorganisms), P1 (addition 5ml/L of B-DECO3 microorganisms), P2 (addition 10 ml/L of B-DECO3 microorganisms), P3 (addition 15ml/L of B-DECO3 microorganisms), P4 (addition 20 ml/L of B-DECO3 microorganisms). The data obtained were analyzed statistically using Anova and DNMRT at 5 % level. The result showed that the addition of microorganism B-DECO3 had significant affect for COD, BOD, TSS, oil, and pH. The treatment chosen from the result of this research was the P4 treatment which had a value of COD (330,63 mg/L), BOD (94,53 mg/L), TSS (266,46 mg/L), Oil (2,50) and pH (8,64).